Fractional responses with spatial dependence of Portuguese wineries’ domestic market sales to an exogenous shock (Covid-19) - Samuel Faria; João Rebelo; Alexandre Guedes; Sofia Gouveia (Wine Economics and Policy)
This paper uses firm-level data to investigate the resilience of the Portuguese wine sector’s domestic market in the aftermath of the exogenous shock arising from Covid-19. To address this objective, this article applies a fractional response model. The results allow us to confirm that the impact of the pandemic crisis depends on firm structure and behaviour reflected by variables such as firm size, age, export intensity, market channel as well as on the geographic location of firms. This suggests the need for the development of innovative regional clusters and calls for managers and policymakers to consider the heterogeneity of wineries and dissimilar effects of contingency measures at the municipal level during an exogenous shock.